2019
DOI: 10.3390/molecules24112192
|View full text |Cite
|
Sign up to set email alerts
|

The PPARγ Agonist Rosiglitazone Suppresses Syngeneic Mouse SCC (Squamous Cell Carcinoma) Tumor Growth through an Immune-Mediated Mechanism

Abstract: Recent evidence suggests that PPARγ agonists may promote anti-tumor immunity. We show that immunogenic PDV cutaneous squamous cell carcinoma (CSCC) tumors are rejected when injected intradermally at a low cell number (1 × 106) into immune competent syngeneic hosts, but not immune deficient mice. At higher cell numbers (5 × 106 PDV cells), progressively growing tumors were established in 14 of 15 vehicle treated mice while treatment of mice with the PPARγ agonist rosiglitazone resulted in increased tumor reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…1 tumours generated after a subcutaneous injection of 1 × 10 4 MC38 cells resulted in an immune response leading to decreased growth and rejection. Because higher numbers of inoculated cells can result in diminished anti-tumour immune responses 45 we injected 2 × 10 5 MC38 cells and did not see rejection or even differences in tumour growth in WT and Fgf2 LMW−/− mice ( Fig. 7a, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 tumours generated after a subcutaneous injection of 1 × 10 4 MC38 cells resulted in an immune response leading to decreased growth and rejection. Because higher numbers of inoculated cells can result in diminished anti-tumour immune responses 45 we injected 2 × 10 5 MC38 cells and did not see rejection or even differences in tumour growth in WT and Fgf2 LMW−/− mice ( Fig. 7a, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For p16 Ink4a , rabbit polyclonal anti-p16 (1:100, M-156, Santa Cruz Biotechnology) was utilized. Immunofluorescence labeling for pan-cytokeratin expression was performed as previously detailed 31 . Chromogenic immunolabeling using DAB as a substrate was done for p53 immunolabeling.…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro study on two breast cancer cell lines (A2780, SKOV3) revealed severe apoptosis and tumor growth inhibition in mouse xenografts after combined therapy of rosiglitazone and olaparib [176]. Rosiglitazone also decreased proliferation and tumor size in human squamous cell carcinoma (SCC) xenografts [177]. In turn, Lau et al demonstrated the synergistic impact of rosiglitazone on 5-fluorouracil-induced apoptosis of two colorectal cancer cell lines (HCT-116, HT-29).…”
Section: Carcinogenesis Modulators: From Basic Research To Clinical Pmentioning
confidence: 99%